Thermoeconomic evaluation and exergy efficiency of dissipative components: A new approach (2018)
Thermoeconomic evaluation alms at diagnosing the malfunction of energy systems and at optimizing their structure and performance. One of the main limitations of this approach is the adequate treatment of dissipative components, i e, components where exergy is destroyed without gaining thermodynamically useful output (condensers, throttling valves, etc.). Such components are contituents of some energy systems and influence their overall thermal efficiency. This research introduces the use of a different criterion of exergy efficiency to assess dissipative components. In this case, it is possible to define the efficiency of dissipative components without the introduction of negentropy flows. As case study, a Rankine cycle discussed in literature is selected. The dfferent approaches to evaluate dissipative components are applied and compared with the proposed one. Results show that with the proposed approach it is possible to evaluate dissipative components in isolation avoiding the incomistencies resulting from the use of negentropy flows in the assessment.